Homocystein levels in menopausal women from Lima, Peru - Vargas Chávez, Marlene (2012)
Abstract Objectives: To compare serum homocysteine levels according to menopausal status in a group of women. Design: Descriptive study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Women 40 to 60 year-old. Interventions: The menopausal status was determined clinically and by serum FSH and estradiol in 97 women 40 to 60 year-old attended at San Bartolome Hospital, Lima, Peru. Plasma homocysteine was determined by fluorescence polarization immunoanalysis. Main outcome measures: Homocysteine levels. Results: Homocysteine levels were within international referential values (5-15 μmol/L). Postmenopausal women levels were significantly higher compared to premenopausal women levels (p< 0.05). Conclusions: Homocysteine levels are increased in menopausal women and could be considered in cardiovascular disease prediction.